Exogenous Abscisic Acid Promotes Anthocyanin Biosynthesis and Increased Expression of Flavonoid Synthesis Genes in Vitis vinifera × Vitis labrusca Table Grapes in a Subtropical Region - Koyama, Renata; Roberto, Sergio R.; de Souza, Reginaldo T.; Borges, Wellington F. S.; Anderson, Mauri; Waterhouse, Andrew L.; Cantu, Dario; Fidelibus, Matthew W.; Blanco-Ulate, Barbara (Frontiers in Plant Science, 2018)
Hybrid (Vitis vinifera × Vitis labrusca) table grape cultivars grown in the subtropics often fail to accumulate sufficient anthocyanins to achieve good uniform berry color. Growers of V. vinifera table grapes in temperate regions generally use ethephon and, more recently, (S)-cis-abscisic acid (S-ABA) to overcome this problem. The objective of this study was to determine if S-ABA applications at different timings and concentrations have an effect on anthocyanin regulatory and biosynthetic genes, pigment accumulation, and berry color of the Selection 21 cultivar, a new V. vinifera × V. labrusca hybrid seedless grape that presents lack of red color when grown in subtropical areas. The application of S-ABA 400 mg/L resulted in a higher accumulation of total anthocyanins and of the individual anthocyanins delphinidin, cyanidin, petunidin and peonidin-3-glucoside in the berry skin and improved the color attributes of the berries. Treatment with two applications at 7 days after véraison (DAV) and 21 DAV of S-ABA 400 mg/L resulted in a higher accumulation of total anthocyanins in the skin of berries and increased the gene expression of CHI, F3H, DFR and UFGT and of the VvMYBA1 and VvMYBA2 transcription factors of the seedless grape Selection 21.